Benchmarking of Databases for Big Data Exploration in the Social Graph Analysis - Węcel, Krzysztof; Perkowski, Bartosz; Filipowska, Agata; Węckowski, Dawid; Zwolenkiewicz, Piotr (Studia Oeconomica Posnaniensia, 2017)
In this article we present the results of the benchmarking of various data and knowledge-based systems for use while analysing a big social graph. MySQL, Neo4J, Titan and Virtuoso have been tested on data describing communication events among ca. 7 million users. We have proposed queries regarding the real-world scenarios derived from the requirements analysis of the data owner. Execution time has been measured for basic, aggregation, and networking types of queries. While MySQL was good at queries requiring calculations, Virtuoso outperformed it in graph-related queries.